The Future of Aging is Florida - Jeffrey Dwyer (EDIS)
Currently, Florida ranks first in the United States in the percent of the population who is full-time and seasonal residents over the age of 65. Older Floridians, their families and communities face a myriad of issues related to aging. This document is FCS2209 FY624, one of a series of publications from the distance education in-service "Aging in the 21st Century." First published: September 2003.